2014
DOI: 10.1162/jocn_a_00604
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Semantic Structure of Cognitive Neuroscience

Abstract: Abstract■ Cognitive neuroscience, as a discipline, links the biological systems studied by neuroscience to the processing constructs studied by psychology. By mapping these relations throughout the literature of cognitive neuroscience, we visualize the semantic structure of the discipline and point to directions for future research that will advance its integrative goal. For this purpose, network text analyses were applied to an exhaustive corpus of abstracts collected from five major journals over a 30-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Thus, our relational mapping of cognitive functions provides a whole picture of cognition which is feasible because it includes many known neurocognitive relationships. A study to survey relationships among cognitive functions whose aim was similar to ours was conducted using text analysis of neuroscience literature (Beam et al, 2014). In this study, the authors identified networks among 100 cognitive concepts, among 100 anatomical regions, and among combinations of both on the basis of the co-occurrences of the terms in the texts.…”
Section: Implications Of the Results And Comparisons With Previous Stmentioning
confidence: 99%
“…Thus, our relational mapping of cognitive functions provides a whole picture of cognition which is feasible because it includes many known neurocognitive relationships. A study to survey relationships among cognitive functions whose aim was similar to ours was conducted using text analysis of neuroscience literature (Beam et al, 2014). In this study, the authors identified networks among 100 cognitive concepts, among 100 anatomical regions, and among combinations of both on the basis of the co-occurrences of the terms in the texts.…”
Section: Implications Of the Results And Comparisons With Previous Stmentioning
confidence: 99%
“…Variations of this network metaphor for knowledge have appeared in philosophy (9), social studies of science (10-12), artificial intelligence (13), complex systems research (14), and the natural sciences (7,15,16). Nevertheless, networks have rarely been used to measure scientific content (2,11,17,18) and never to evaluate the efficiency of scientific problem selection.In this paper, we build a model of scientific investigation that allows us to measure collective research behavior in a large corpus of scientific texts and then compare this inferred behavior with more and less efficient alternatives. We define an explicit objective function to quantify the efficiency of a research strategy adopted by the scientific community: the total number of experiments performed to discover a given portion of an unknown knowledge graph.…”
mentioning
confidence: 99%
“…Variations of this network metaphor for knowledge have appeared in philosophy (9), social studies of science (10)(11)(12), artificial intelligence (13), complex systems research (14), and the natural sciences (7,15,16). Nevertheless, networks have rarely been used to measure scientific content (2,11,17,18) and never to evaluate the efficiency of scientific problem selection.…”
mentioning
confidence: 99%
“…The authors used the network to draw connections between human innovation process and random walks. In the field of neuroscience, semantic networks have been used to map the landscape of the field [11,12]. Papers from the interdisciplinary journal PNAS have been used to investigate sociological properties such as inter-disciplinary research [13].…”
Section: Introductionmentioning
confidence: 99%